Implementasi Manajemen Talenta di Kantor Kecamatan Tanah Grogot Kabupaten Paser - Amir Hamzah; Muhammad Akbar; Tegen Sayuk Rimboko; Erni Susanti; Yunus Syam; Achmad Syahruddin (Universitas Kristen Indonesia Toraja, 2025)
This service aims to socialize the application of Talent Management in the Tanah Grogot District Office, Paser Regency. This service method is qualitative. The results of this service include several stages. The talent identification stage is the initial stage that must be prepared and implemented in implementing talent management. This stage is a strategy for obtaining talent which is implemented through the critical job analysis stage. The second stage is talent placement and evaluation. The placement of talents into target positions is carried out based on a predetermined succession plan. Periodically, the talent committee updates the identification of positions that will be vacant and must be immediately succeeded by new officials